Neuro-Wireless Vehicle’s Movement Control (Journal of the College of Basic Education, 2022)
The aim of this paper is to control the movements of a vehicle wireless by using two ways: either to move in the four main directions through the keyboard of a computer, or to force the vehicle to move through a desired path by training the multi-layer feed forward neural network. This was done under three phases; the first phase was to design a specific hardware represented by an electronic board, which represents the transmission circuit to be interfaced with the computer to control the movement of the vehicle wirelessly, while the second phase was to implement a specific software to control the movement which was programmed by using the visual basic object oriented language, the third phase was to train the multi-layer feed forward neural network by the backpropagation learning algorithm to estimate the desired path of the vehicle’s movement, then to control the movement of the vehicle according to the desired path.